Answer:
1)
82.5 - <u>8</u><u>2</u><u>.</u><u>5</u> + 2x = 338.5 - <u>8</u><u>2</u><u>.</u><u>5</u>
<u>2</u>x = <u>2</u><u>5</u><u>6</u>
2)
2x ÷ <u>2</u> = 256 ÷ <u>2</u>
x = <u>1</u><u>2</u><u>8</u>
Step-by-step explanation:
1)
In order to get rid 82.5, you have to substract the same value on both side to get a 0 value.
2)
In order to find the value of x, you have to divide the value that is sticked with x which is 2. As you divide 2 by 2, you will get 1 as a single value of x so you have to divide 2 to both side too.
<em>2 solutions</em>
<em>X= 16</em>
<em>X=49</em>
Step-by-step explanation:
<em>original equation</em>
<em>x-11√x+28 = 0</em>
<em> Isolate</em>
<em> -11√x = -x-28+0</em>
<em> Tidy up</em>
<em> 11√x = x+28</em>
<em> Raise both sides to the second power</em>
<em> (11√x)2 = (x+28)2</em>
<em>After squaring</em>
<em> 121x = x2+56x+784</em>
<em> Plug in 49 for x </em>
<em> 11√(49) = (49)+28</em>
<em>Simplify</em>
<em> 11√49 = 77</em>
<em> Solution checks !!</em>
<em> Solution is:</em>
x = 49
<em>Plug in 16 for x </em>
<em> 11√(16) = (16)+28</em>
<em>Simplify</em>
<em> 11√16 = 44</em>
<em> Solution checks !!</em>
<em> Solution is:</em>
x = 16
Answer:
not helping you i will take the points tho.
Step-by-step explanation:
thanks for the points im taking them back now c: this is what you get for messing with me
(x+3y) (x-3y) = x^2 9y^2
(x-y) (x+3y) = x^2+2xy-3y^2
(xy+9y+2) (xy-3) = x^2 y^2 +9xy^2-xy-27y-6
(x^2+3xy-2) ( xy+3) = x^3 y+3x^2 y^2 +7xy-6
(2xy+x+y) (3xy^2-y) = 6x^2 y^3 +3x^2 y^2 +xy^2-2xy^2-xy-y^2
(xy+3x+2) ( xy-9) = x^2 y^2 +3x^2 y -7xy-27x-18
Answer:
1. 2x+2-(2x-14)=5x+2
0x+16=5x+2
16=5x+2
14=5x
14/5=x or 2.8=x
2. 2x+10-(-2x+7)=-7x+14
4x+3=-7x+14
11x+3=14
11x=11
x=1
Step-by-step explanation:
Hope this helps